Optimalisasi Rute Pengiriman Dengan Meminimasi Jarak Menggunakan Saving Matrix: Sebuah Studi Kasus - Sepadyati, Nova; Hariono, Ronny; Xaverius Nelson Thesman , Fransiskus; Renard Leuw, Raynaldy; Edric, William; Vincent , Hananiel (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
CV. X is a pillows and bolsters manufacturer in Surabaya. The current deliverystrategy is a single route using limited-capacity vehicles. Single route deliverymakes low % utilization or multiple deliveries to the same customer daily. Thepurpose of this case study is to find the minimum cost route with a specificvehicle and limited capacity using the Saving Matrix method and make asuggestion by creating an SOP for product delivery. After calculating the pastdata from July to September 2022, a distance savings of 12.11 km was obtained,and the highest savings in the number of transport vehicles was 2. In addition,there was a 20% increase in truck utilization.